2012
DOI: 10.3109/00365521.2012.688213
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab modifies mesenteric adipose tissue alterations and intestinal inflammation in rats with TNBS-induced colitis

Abstract: Our results suggest that infliximab could contribute to the control of intestinal inflammation by modifying adipokine production by mesenteric adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…In a recent study, methotrexate treatment was found to be associated with the decreased production of inflammatory adipokines in reactivated animal colitis [68]. In addition to control intestinal inflammation, infliximab treatment could restore the adipocyte morphology and PPAR-g expression [69]. In line with previous reports, our data Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study, methotrexate treatment was found to be associated with the decreased production of inflammatory adipokines in reactivated animal colitis [68]. In addition to control intestinal inflammation, infliximab treatment could restore the adipocyte morphology and PPAR-g expression [69]. In line with previous reports, our data Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Extensive accumulation of inflammatory cells was not observed in colon tissue of UNPtreated animals. Furthermore, consequently, there was a lesser accumulation of MPO in the colon tissue of the UNP-treated group of animals as observed from tissue biochemical analysis (Figure 8a), which can be corroborated by other studies (Clemente et al, 2012;Takagi et al, 2012). The UNPs reached the colon and maintained a constant level of drug in colon and delivered the total drug load that prevented ulcer formation showing the protective efficacy of UDCA (de Souza Almeida et al, 2011).…”
Section: In Vivo Efficacy Studysupporting
confidence: 85%
“…6A). Monoclonal antibodies against TNF-␣ ameliorate inflammation and improve mucosal healing in animal models of experimental colitis (12,58). We predicted that, independent of sex and CRF 2 levels, administration of therapeutic monoclonal anti-TNF-␣ antibody should reduce inflammation.…”
Section: -Test)mentioning
confidence: 99%